Biomass & bioenergy IEA bioenergy: Update 72 - Paul Bennett; Jan Liebetrau; Uwe Fritsche (Biomass and Bioenergy, 2023)

Process-oriented Basic Data for Environmental Management Instruments - www.probas.umweltbundesamt.de - Uwe Fritsche (The International Journal of Life Cycle Assessment, 2005)

Comparison of Plastic Packaging Waste Management Options: Feedstock Recycling versus Energy Recovery in Germany - Volrad Wollny; Günter Dehoust; Uwe R. Fritsche; Peter Weinem (Journal of Industrial Ecology, 2001)
Summary Plastics recycling, especially as prescribed by the German Ordinance on Packaging Waste (Verpackungsverordnung), is a conspicuous example of closing material loops on a large scale. In Germany, an industry‐financed system (Duales System Deutschland) was established in 1991 to collect and recycle packaging waste from households. To cope with mixed plastics, various “feedstock‐recycling” processes were developed. We discuss the environmental benefits and the cost‐benefit ratio of the system relative to municipal solid waste (MSW) incineration, based on previously published life‐cycle assessment (LCA) studies. Included is a first‐time investigation of energy recovery in all German incinerators, the optimization opportunities, the impact on energy production and substitution processes, an estimation of the costs, and a cost‐benefit assessment. In an LCA, the total environmental impact of MSW incineration is mainly determined by the energy recovery ratio, which was found on average to reach 39% in current German incineration plants. Due to low revenues from additional energy generation, it is not cost‐effective to optimize the plants energetically. Energy from plastic incineration substitutes for a specific mixture of electric base‐load power, district heating, and process steam generation. Any additional energy from waste incineration will replace, in the long term, mainly natural gas, rather than coal. Incineration of plastic is compared with feedstock recycling methods in different scenarios. In all scenarios, the incineration of plastic leads to an increase of CO2 emissions compared to landfill, whereas feedstock recycling reduces CO2 emissions and saves energy resources. The costs of waste incineration are assumed to decrease by about 30% in the medium term. Today, the calculated costs of CO2 reduction in feedstock recycling are very high, but are ex‐pected to decline in the near future. Relative to incineration, the costs for conserving energy via feedstock recycling are 50% higher, but this gap will close in the near future if automatic sorting and processing are implemented in Germany.